Diagnosis and Treatment of Celiac Disease - Oktadiana, Harini; Abdullah, Murdani; Renaldi, Kaka (UI Scholars Hub, 2017)
Celiac disease is a reversible, proximal immune enteropathy resulting from the interaction of dietary gluten with the intestinal immune system. Celiac disease can produce varied manifestations and may develop at any age. New cases have increased substantially, due to increase awareness and better diagnostic tools. Standard diagnosis of celiac disease is based on positive serologic tests and histopathologic examination of duodenal biopsies. Treatment of celiac disease with free gluten diet will improve symptoms, quality of life, reduce risk of malignancy and complication. Nowadays, treatment strategy of celiac disease with non-dietary therapies is still underdevelopment.